CORRELATION BETWEEN CD4 LYMPHOCYTES, VIRAL LOAD AND L-LYSINE PLASMA LEVEL IN HIV-INFECTED PATIENTS - Butorov, E. V. (Infekt͡s︡ii͡a︡ i immunitet, 2015)
Introduction.HIV-infection is associated with significant pathological changes of the host metabolic processes, such as energy dysfunction, dyslipidemia, protein catabolic effects and amino acid imbalance, which ultimately form the polymorphism of clinical symptoms of the disease. The significant disturbances of protein and lipid metabolism are widely described in asymptomatic and advanced stage HIV-infected patients, but infection-related amino acid abnormalities is not fully explored. The further research of HIV impact on the host metabolic processes in particular, the plasma amino acid profile, are essential for understanding the pathophysiology of HIV-infection. Our aim was to determine the association between CD4 lymphocytes, viral load and plasma L-lysine levels in clinical stages HIV-infected patients. Material and methods.A total of 750 HIV-1-infected males before highly active antiretroviral therapy (HAART) monitored in our center. The patients were classified into four stages of the disease 3, 4a, 4b and 4c, according to the classification system for HIV-infection in Russian Federation (2006). Quantitative HIV-1 RNA assay was performed using (RT-PCR) reverse-transcriptase polymerase chain reaction. The plasma L-lysine levels were assessed by thin layer chromatography (TLC). Results. We observed that plasma L-lysine concentrations markedly decreased with the clinical stages of HIV-infection. Low levels of essential amino acid were found in 57% of HIV-infected subjects in the asymptomatic stage (3), 67% and 68% in the advanced stages (4a and 4b, 4c, respectively). Our data revealed that plasma amino acid concentrations were positively correlated with CD4 count lymphocytes (P 0.01) and inversely with HIV viral load (P 0.05) in the total cohort. The mean L-lysine acid levels were significantly lower in advanced stage (4a and 4b, 4c) HIV-infected patients than in controls and asymptomatic stage (3) patients (P 0.01 and P 0.001, respectively). Conclusion. There was evidence of the association between plasma L-lysine and HIV-1 RNA level, immunological markers and clinical stages of HIV-infection among the entire cohort. The results show that advanced stages of HIV-infection are characterized by significant changes in plasma L-lysine concentrations with the disease stages of HIV-infection. Levels of this basic amino acid negatively correlating with viral load and inversely with CD4 count lymphocytes. These findings are important for understanding the pathophysiology of HIV-infection and the development of new approaches in the treatment. Although the mechanism is at present conjectural, the influence of plasma L-lysine on the HIV-1 RNA levels must be considered and remains to be proved.